Neck-to-height ratio is positively associated with diabetic kidney disease in Chinese patients with type 2 diabetes mellitus - He, Zhi-Ying; Gu, Xiao; Du, Lin-Jia; Hu, Xiang; Zhang, Xing-Xing; Yang, Li-Juan; Li, Ying-Qian; Li, Jing; Pan, Lin-Yu; Yang, Bo; Gu, Xue-Jiang; Lin, Xiu-Li (Frontiers in Endocrinology, 2023)
Introduction: The aim of this study was to investigate the associations of neck circumference (NC) and neck-to-height (NHR) with diabetic kidney disease (DKD) in Chinese patients with type 2 diabetes mellitus (T2DM). Materials and Methods: A total of 2,615 patients with prevalent T2DM were enrolled. NHR was calculated through NC (cm) divided by height (cm), and prevalent DKD was defined as the urinary albumin-to-creatinine ratio (UACR) ≥ 30 mg/g or the estimated glomerular filtration rate (eGFR) < 60 ml/min per 1.73 m2 in the absence of other primary kidney diseases. Results: The levels of NC and NHR were higher in DKD patients compared with non-DKD patients (38.22 vs. 37.71, P = 0.003; 0.232 vs. 0.227, P < 0.001, respectively). After full adjustments, individuals at the highest tertile of NHR had higher odds of DKD than those at the lowest tertile (multivariate-adjusted OR = 1.70, 95% CI: 1.28, 2.26), but this association was not pronounced with NC (multivariate-adjusted OR = 1.29, 95% CI: 0.91, 1.83). Individuals at the highest tertile of NHR had lower eGFR (β = -5.51, 95% CI: -7.48, -3.54) and higher UACR levels (β = 0.31, 95% CI: 0.13, 0.49) than those at the lowest tertile. The adverse association between NHR and prevalent DKD remained statistically significant among most of the subgroups analyzed and no interaction effects were observed. Conclusion: The increase in NHR was adversely and independently associated with DKD in this Chinese T2DM population.